Quantization of edge currents of continuous magnetic operators - Kellendonk, Johannes; Schulz-Baldes, Hermann (Journal of Functional Analysis, 2004)
For a magnetic Hamiltonian on a half-plane given by the sum of the Landau operator with Dirichlet boundary conditions and a random potential, a quantization theorem for the edge currents is proven. This shows that the concept of edge channels also makes sense in presence of disorder. Moreover, Gaussian bounds on the heat kernel and its covariant derivatives are obtained. © 2003 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dma.pma22.quanti